Pengembangan Kompetensi Keagamaan Remaja Muslim di Madrasah Aliyah Hidayatul Muslimin 2: Pelatihan Khatib dan Ilmu Tajwid - Ahmad Akbar; Septian Purba Wijaya; Sendu Junintias; Masadah; Sukino (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of religious competence in Muslim adolescents is important in forming strong character and faith. This study aims to examine the effectiveness of khatib and tajwid training in improving the religious competence of students at Madrasah Aliyah Hidayatul Muslimin 2. The method used is Community Based Research (CBR) which involves the active participation of students and teachers in the design, implementation, and evaluation of training. Data were collected through observation, interviews, and skills tests. The results of the study showed a significant increase in the mastery of tajwid and the ability to preach, which had an impact on increasing students' self-confidence and active role in religious activities in the madrasah and the community. These findings indicate that ongoing training with a participatory approach is effective for developing adolescent religious competence and can be a model for developing religious education in other madrasahs.